Japan’s South China Sea Policy and Regional Subcomplex Expansion: Toward Free and Open Indo-Pacific - Irsadanar, Rafyoga Jehan Pratama (Jurnal Hubungan Internasional, 2021)
This research aims to investigate Japan’s motivation to be involved in the South China Sea dispute despite Japan’s far distance from the conflicted area. Utilizing the qualitative research method, this research analyzes Japanese Government official documents and relevant literature to achieve the research objective. The research discovers that Japan’s main interest in the South China Sea is to articulate a safer maritime lane for the sake of its Free and Open Indo-Pacific agenda by balancing China’s assertiveness in the region. Employing a regional security complex framework, this research sees that Japan, by its presence in the South China Sea, tries to intensify the security interaction with Southeast Asian counterparts to expand the Northeast Asian regional subcomplex, aiming to strengthen the perception of China as a threat to Southeast Asian countries. The South China Sea involvement will fortify Japan’s security interlink with Southeast Asian counterparts, balancing China’s expansive trait in the maritime zone, accelerating Tokyo-initiated Free and Open Indo-Pacific vision.